Analysis of transition metal complexes formed through contact of skin with circulating coins and metabolipidomic changes induced by dermal nickel penetration determined in an ex vivo porcine ear skin model - Rezaei, Azar; Justus Liebig University Giessen (My University, 2024)
Nickel allergic contact dermatitis (Ni-ACD) is the most common delayed-type hypersensitivity reaction affecting the skin worldwide, yet the underlying mechanisms remain elusive. This study presents a novel approach combining tandem mass spectrometry (MS/MS) and matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) to shed light on these interactions: The MS/MS analysis of metal complexes on 1-euro coins, a prevalent nickel, copper, and zinc source, unveiled their distribution with micrometer precision. A notable result from atmospheric pressure laser desorption/ionization mass spectrometry imaging (AP-LDI MS) imaging of a cleaned 1-Euro coin is the detection of signals at m/z 207.8941 ([C4HO3NNi+K]+) and m/z 116.9527 ([CH4NZn+Na]+). Furthermore, we delved into the impact of simulated sweat components such as lactic acid, urea, and sodium chloride on metal dissolution, leading to the discovery of a unique copper complex at m/z 140.9728 [Cu(CH4N2O)+H2O]+. Notably, the concentration of metal ions increased on the surface of coins treated with artificial sweat solutions compared to cleaned Euro coins, especially nickel metal ions. Following the developing method for investigating metal ions, the MALDI MSI analysis of ex vivo porcine ear skin exposed to increasing nickel concentrations revealed the spatial distribution of nickel-induced metabolic alterations. We further investigated nickel penetration using the dimethylglyoxime (DMG) staining method. This method showed that most nickel ions were confined to the stratum corneum for lower nickel concentrations (up to 84 µg/cm²). Interestingly, areas with high nickel accumulation within the stratum corneum exhibited decreased levels of arginine and ceramides. Meanwhile, the deeper viable epidermis and dermis showed downregulation of specific lipids such as phosphatidylcholines and sphingomyelins. These findings advance our understanding of metal allergens and highlight the potential impact of sweat composition on increasing metal ions, which leads to metal allergy development. Moreover, the research provides direct insights into the effect of common metal allergens on skin metabolites and lipids. This underscores the need for further research to delve into the mechanisms of metal penetration and their effects on skin composition, which could potentially revolutionize treatment options for metal sensitivity and enhance the quality of life for individuals with metal allergies.
Keywords: ddc:540